A Price Theory of Multi-Sided Platforms: Comment - Tan, Hongru; Wright, Julian (American Economic Review, 2018)
Weyl (2010) shows that in multi-sided platform settings, profit maximization leads to classical and Spence distortions, with the Spence distortion providing a new explanation for why prices may sometimes be too high (or too low) on platforms. However, the key formulas that Weyl gives comparing privately and socially optimal prices are misstated. Properly interpreted, his results only explain marginal incentives with respect to setting prices but not the total distortion in prices, which can be very different. (JEL D42, D85, L12, L14)